Association of remnant cholesterol and lipid parameters with new-onset carotid plaque in Chinese population - Liu, Bo; Fan, Fangfang; Zheng, Bo; Yang, Ying; Jia, Jia; Sun, Pengfei; Jiang, Yimeng; Li, Kaiyin; Liu, Jiahui; Chen, Chuyun; Li, Jianping; Zhang, Yan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Remnant lipoprotein cholesterol (RC) is an independent risk factor for cardiovascular disease (CVD). However, the relationships of remnant cholesterol and other conventional lipid parameters with new-onset carotid plaque are not fully understood in the Chinese community-based population. Methods: A total of 872 plaque-free participants (51.39 ± 4.96 years old) with no history of CVD were included in this study. The plasma concentrations of RC were calculated by subtracting low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) from total cholesterol (TC). Multivariate regression models were used to evaluate and compare the associations between RC and other lipid parameters and new-onset carotid plaque. Results: After a mean 6.77-year follow-up, the incidence of new-onset carotid plaque was 188 (21.56%). RC was significantly associated with new-onset carotid plaque [Odd ratio (OR)=1.57 per 1 mmol/L increase, 95% confidence interval (CI): 1.03-2.41, p =0.038]. The highest tertile of RC (T3 group) had the highest risk of new-onset carotid plaque (OR =2.53, 95% CI: 1.63-3.95). Similar results were seen for increased other lipid parameters, but decreased HDL-C levels. When adding another lipid parameter into the adjusted model with RC simultaneously, only RC remained significantly associated with new-onset carotid plaque after adjusting for other lipid parameters (all p value <0.005). Furthermore, RC was strongly associated with new-onset carotid plaque in participants with lower baseline LDL-C levels. Conclusions: Increased RC levels were superior to other conventional lipid parameters to be associated with new-onset carotid plaque in the Chinese community-based population. Furthermore, RC should be considered in participants with lower LDL-C levels for the purpose of early atherosclerosis prevention.